Three-dimensional porous carbon composite material, preparation method, negative electrode and battery

By using three-dimensional porous carbon composite materials in the negative electrode of the battery, the problems of volume changes and dendrite generation during the charging and discharge process of alkali metal negative electrodes are solved, and higher cycle life and safety performance are achieved.

CN119833611APending Publication Date: 2025-04-15CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510036010.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing alkali metal negative electrodes have severe volume changes and dendrites during charging and discharge, affecting the safety performance of the battery.

Method used

A three-dimensional porous carbon composite material is used as the negative electrode material, and prepared by spray drying and carbonization treatment to form a three-dimensional porous carbon skeleton with uniform pores and high specific surface area, and alkali-philic metal metal elements or metal phosphide particles are embedded inside it.

Benefits of technology

Through the three-dimensional porous structure design, the expansion of the negative electrode and the formation of dendrites are reduced, the cycle life and safety performance of the battery are improved, and the rate performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833611A_ABST
    Figure CN119833611A_ABST
Patent Text Reader

Abstract

The invention relates to a three-dimensional porous carbon composite material, a preparation method, a negative electrode and a battery, and the preparation method comprises the following steps: stirring and mixing a metal hydroxide and a water-soluble organic matter in water to obtain a slurry, the metal hydroxide comprising a hydroxide of an alkali-loving metal element; performing spray drying on the slurry to obtain a spray drying product; and under the protective atmosphere, the spray drying product is subjected to carbonization treatment, the three-dimensional porous carbon composite material is obtained, and the three-dimensional porous carbon composite material comprises a three-dimensional porous carbon skeleton and elemental particles of alkali metal-philic metal elements embedded in the three-dimensional porous carbon skeleton. The problem that the safety performance of the battery is influenced by serious volume change and dendritic crystal generation of the existing alkali metal negative electrode in the charging and discharging process can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a three-dimensional porous carbon composite material, a preparation method, a negative electrode and a battery. Background Art

[0002] With the consumption of fossil energy such as oil, environmental problems have gradually become prominent, and the development of renewable energy has also been strengthened. How to convert renewable energy into secondary energy for storage is also a key link in energy utilization, and battery energy storage is the most important way.

[0003] Among the commercial lithium batteries, the most commonly used negative electrode material graphite has a theoretical capacity of only 372mAh / g, which is gradually unable to meet the current growing demand for high energy density power and energy storage batteries. Lithium metal has a theoretical capacity of 3860mAh / g. -1 With its high capacity density and low voltage of -3.04V (relative to standard hydrogen electrode), it is considered to be the most promising negative electrode material for the next generation. However, on the one hand, all alkali metals, including lithium, will produce dendrites due to uneven deposition at the electron-ion interface. Such dendrites can easily pierce the diaphragm, causing battery short circuits and leading to safety accidents such as fire and explosion. On the other hand, lithium metal undergoes huge volume changes during repeated charge and discharge processes. This volume change will cause the SEI film to continuously rupture and regenerate, consuming the electrolyte while making it difficult to form a stable solid-liquid interface. These two problems have seriously hindered the practical application of metal lithium batteries.

[0004] The prior art proposes some improved methods.

[0005] Some researchers have proposed a method of using porous carbon materials as negative electrodes to achieve the purpose of lithium deposition. For example, materials such as carbon sources, conductive agents, lithium-philic agents and catalysts are mixed, and a porous carbon microsphere is prepared by spray drying and annealing carbonization. The porous carbon microsphere has a three-dimensional open pore structure, which provides deposition space for metallic lithium, reduces the volume effect, and alleviates expansion. The lithium-philic substances are evenly distributed in the porous carbon microspheres, which can optimize the lithium deposition sites and attract lithium to be evenly deposited, thereby alleviating the growth of dendrites. However, the above invention only uses carbonization treatment after mixing the materials, and the resulting porosity is limited, so the negative electrode still has a high volume expansion, which in turn affects the cycle life.

[0006] At the same time, some researchers choose to prepare negative electrodes by combining metallic lithium and graphite. For example, nano-modified metal skeleton materials are prepared by graphite and metal salts, and lithium metal is embedded in the metal nano-modified graphite by electrodeposition as the negative electrode of the battery. The gaps between graphite are cleverly used as lithium insertion sites. The amount of lithium insertion is increased by interlayer insertion and then surface deposition, thereby improving the negative electrode capacity. However, the size of the pore structure between the above graphite cannot be adjusted, and the dispersion problem of metallic lithium is difficult to solve, so it cannot be used in practice.

[0007] In general, although the existing technology has made certain progress and development, there are still problems such as uneven lithium metal deposition, large volume expansion, expensive raw materials, and high costs. Summary of the invention

[0008] The embodiments of the present application provide a three-dimensional porous carbon composite material, a preparation method, a negative electrode and a battery to solve the problem that the existing alkali metal negative electrode has serious volume changes and generates dendrites during the charge and discharge process, affecting the safety performance of the battery.

[0009] In a first aspect, a method for preparing a three-dimensional porous carbon composite material is provided, comprising:

[0010] Mixing a metal hydroxide and a water-soluble organic matter in water by stirring to obtain a slurry, wherein the metal hydroxide includes a hydroxide of a metal element that is alkali-philic;

[0011] spray drying the slurry to obtain a spray-dried product;

[0012] The spray-dried product is carbonized under a protective atmosphere to obtain a three-dimensional porous carbon composite material.

[0013] In some embodiments, the alkali-philic metal element includes silver (Ag).

[0014] In some embodiments, the hydroxide of the metal element of the alkali-philic metal is silver hydroxide;

[0015] The preparation method further comprises the following steps of preparing a metal hydroxide:

[0016] Adjusting ammonia water to a preset pH value to obtain a base solution;

[0017] Adding a mixed solution containing a soluble salt of a base metal and silver nitrate to the base solution, and adding ammonia water to generate a complex and a precipitate;

[0018] Aging, filtering, washing and drying can obtain metal hydroxide.

[0019] In some embodiments, the concentration of the ammonia water is 0.02 mol / L to 20 mol / L.

[0020] In some embodiments, the preset pH value is 6-11.

[0021] In some embodiments, the base metal includes one or more of nickel, iron, copper, zinc, aluminum and manganese.

[0022] In some embodiments, the soluble salt of the base metal includes one or more of sulfate and nitrate.

[0023] In some embodiments, the molar ratio of base metal ions to silver ions in the mixed solution is 1:0.1-10.

[0024] In some embodiments, the molar ratio of the total amount of ammonia water to the soluble salt of the base metal is 1:0.05-20.

[0025] In some embodiments, the water-soluble organic matter includes one or more of sucrose, glucose, PVP, sodium carboxymethyl cellulose, polyethylene, polypropylene, mannose, starch, chitosan, dextran, oxalic acid and boric acid.

[0026] In some embodiments, the mass ratio of the metal hydroxide to the water-soluble organic matter is 1:0.01-100.

[0027] In some embodiments, during the carbonization treatment, the heating rate is 0.5-20° C. / min, the calcination temperature is 500-1100° C., and the calcination time is 50-600 min.

[0028] In some embodiments, after the carbonization treatment, the preparation method further comprises:

[0029] Under a protective atmosphere, a phosphating treatment is performed so that the three-dimensional porous carbon composite material further includes metal phosphide particles embedded in the three-dimensional porous carbon framework.

[0030] In some embodiments, the phosphorus source used in the phosphating treatment includes one or more of phosphate, metaphosphate, hypophosphite and phosphorus pentoxide.

[0031] In some embodiments, the mass ratio of the phosphorus source used in the phosphating treatment to the product after the spray-dried product is carbonized is 1:(0.2-50).

[0032] In some embodiments, during the phosphating treatment, the heating rate is 0.5-20°C / min, and the phosphating temperature is 200°C-500°C.

[0033] In some embodiments, after the phosphating treatment, the preparation method further comprises:

[0034] Wash with acid and dry.

[0035] In some embodiments, the acid solution includes one or more of dilute hydrochloric acid, dilute sulfuric acid and glacial acetic acid.

[0036] In a second aspect, a three-dimensional porous carbon composite material is provided, which includes a three-dimensional porous carbon skeleton, and single particles of metal elements of alkaliphilic metals embedded in the three-dimensional porous carbon skeleton, or metal phosphide particles and single particles of metal elements of alkaliphilic metals embedded in the three-dimensional porous carbon skeleton.

[0037] In a third aspect, a three-dimensional porous carbon-alkali metal composite material is provided, comprising:

[0038] A three-dimensional porous carbon composite material as described above, or a three-dimensional porous carbon composite material prepared by any of the methods for preparing a three-dimensional porous carbon composite material as described above;

[0039] and an alkali metal embedded in the three-dimensional porous carbon framework.

[0040] In a fourth aspect, a method for preparing the three-dimensional porous carbon-alkali metal composite material as described above is provided, comprising:

[0041] The alkali metal is introduced into the three-dimensional porous carbon framework by electrodeposition, electrochemical method or melting method.

[0042] In a fifth aspect, a negative electrode is provided, which includes the three-dimensional porous carbon composite material as described above, and / or the three-dimensional porous carbon-alkali metal composite material as described above.

[0043] In a sixth aspect, a battery is provided, comprising the negative electrode as described above.

[0044] The beneficial effects of the technical solution provided by this application include:

[0045] The spray drying method in the present application has the function of composite balling of the hydroxide of the metal element of the alkali-philic metal and the water-soluble organic matter as the carbon material. The hydroxide of the metal element is decomposed into gas and metal oxide during the carbonization process and is finally reduced to the single particle of the metal element. The generation of gas and the reduction of volume will produce holes inside the carbon material, thereby forming a three-dimensional porous carbon skeleton. The three-dimensional porous carbon skeleton has the advantages of uniform pores, large specific surface area, and high porosity.

[0046] Through the design of the three-dimensional porous structure, the three-dimensional porous carbon skeleton with hollow and porous structure inside provides a location for the deposition of alkali metals, and at the same time reserves space for the volume change of alkali metals during the charge and discharge process, reducing the occurrence of side reactions caused by material breakage, reducing the expansion of the negative electrode, and increasing the cycle life. At the same time, the three-dimensional porous carbon skeleton is evenly distributed with single-substance particles. The embedded single-substance particles can induce the uniform deposition of alkali metals inside the three-dimensional porous carbon skeleton due to their affinity for alkali metals, regulating the uniformity of alkali metal deposition under high current, reducing the formation of dendrites, and improving safety. The high specific surface area of ​​the three-dimensional porous carbon skeleton effectively increases the reaction sites with the electrolyte, thereby improving the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0048] Figure 1 A flow chart of a method for preparing a three-dimensional porous carbon composite material provided in an embodiment of the present application;

[0049] Figure 2 A schematic cross-sectional view of a three-dimensional porous carbon composite material provided in an embodiment of the present application;

[0050] Figure 3 This is a schematic cross-sectional view of a three-dimensional porous carbon-alkali metal composite material provided in an embodiment of the present application.

[0051] In the figure: 11, three-dimensional porous carbon skeleton; 12, pores; 13, single-element particles; 14, alkali metals; 15, metal phosphide particles. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0053] See also Figure 1 As shown, the present invention provides a method for preparing a three-dimensional porous carbon composite material, which comprises the following steps:

[0054] 101: Stirring and mixing a metal hydroxide and a water-soluble organic matter in water to obtain a slurry, wherein the water-soluble organic matter is used as a carbon source to subsequently form a three-dimensional porous carbon skeleton, and the metal hydroxide includes a hydroxide of a metal element of a pro-alkali metal.

[0055] It is understood that the alkali metal includes one or more of lithium, sodium and potassium.

[0056] 102: spray drying the slurry to obtain a spray-dried product.

[0057] 103: Under a protective atmosphere, the spray-dried product is carbonized to obtain a three-dimensional porous carbon composite material, wherein the three-dimensional porous carbon composite material includes a three-dimensional porous carbon skeleton and single particles of metal elements of alkali-philic metals embedded in the three-dimensional porous carbon skeleton.

[0058] The spray drying method in the present application has the function of composite balling of the hydroxide of the metal element of the alkali metal and the water-soluble organic matter as the carbon material. The hydroxide of the metal element is decomposed into gas and metal oxide during the carbonization process, and finally reduced to the single substance particles of the metal element. The generation of gas and the reduction of volume will produce holes inside the carbon material, thereby forming a three-dimensional porous carbon skeleton. The three-dimensional porous carbon skeleton has the advantages of uniform pores, large specific surface area, high porosity, etc. Figure 2 As shown, pores 12 are generated on the three-dimensional porous carbon skeleton 11 due to the action of gas, and single-substance particles 13 are embedded in the pores 12 .

[0059] Through the design of the three-dimensional porous structure, the three-dimensional porous carbon skeleton with hollow pores inside provides a location for the deposition of alkali metal 14, and at the same time reserves space for the volume change of alkali metal 14 during the charge and discharge process, thereby reducing the occurrence of side reactions caused by material breakage, reducing the expansion of the negative electrode, and increasing the cycle life. At the same time, the single substance particles 13 are evenly distributed inside the three-dimensional porous carbon skeleton. The embedded single substance particles 13 are pro-alkali metal 14, and can induce the alkali metal 14 to be uniformly deposited inside the three-dimensional porous carbon skeleton 11, thereby regulating the uniformity of alkali metal deposition under high current, reducing the formation of dendrites, and improving safety. Figure 3 As shown, an alkali metal 14 is embedded in the pores 12. The high specific surface area of ​​the three-dimensional porous carbon skeleton 11 effectively increases the reaction sites with the electrolyte, thereby improving the rate performance of the battery.

[0060] The mass ratio of the metal hydroxide to the water-soluble organic matter can be determined according to actual needs. For example, as an example, the mass ratio of the metal hydroxide to the water-soluble organic matter is 1:0.01-100. Preferably, the mass ratio of the metal hydroxide to the water-soluble organic matter is 1:2.

[0061] As a preferred example, in the present application, the metal element that is alkali-philic includes silver (Ag).

[0062] Accordingly, the hydroxide of the metal element that is alkali-philic is silver hydroxide, and the single substance particles of the metal element that is alkali-philic are silver particles.

[0063] In the present application, the metal hydroxide can be a finished product or can be homemade.

[0064] For example, as an example, the steps of preparing a metal hydroxide include:

[0065] 201: Adjust the ammonia water to a preset pH value to obtain a base solution.

[0066] Specifically, ammonia water of a certain concentration is prepared and then adjusted with an acid such as dilute sulfuric acid.

[0067] The concentration of the ammonia water can be determined according to actual preparation needs, and should not be too low. If the concentration is too low, the pH value of the ammonia water is low and the ability to adjust the pH value is limited. It should not be too high. Ammonia water with too high a concentration is not easy to obtain. For example, as an example, the concentration of the ammonia water is 0.02 mol / L to 20 mol / L.

[0068] The preset pH value can be determined according to actual preparation needs. For example, as an example, the preset pH value is 6-11.

[0069] 202: Add a mixed solution containing a soluble salt of a base metal and silver nitrate to the base solution, and then add ammonia water to generate a complex and a precipitate.

[0070] The base metal includes one or more of nickel, iron, copper, zinc, aluminum and manganese, which can be selected according to actual needs.

[0071] The soluble salt of base metal includes one or more of sulfate and nitrate, which can be selected according to actual needs.

[0072] When preparing the mixed solution, the base metal should not be too much or too little. If the base metal is too much, materials will be wasted, and if it is too little, the silver in it will also be affected by the added ammonia water, reducing the yield. Therefore, the molar ratio of the base metal ions to the silver ions in the mixed solution is 1:0.1~10.

[0073] Meanwhile, in steps 201 and 202, the molar ratio of the total amount of ammonia water to the soluble salt of the base metal is 1:0.05-20.

[0074] 203: Aging, filtering, washing and drying to obtain a metal hydroxide, which includes nano-scale silver hydroxide and a certain amount of base metal hydroxide.

[0075] In this application, NH 3 Combine with base metal ions to form complexes. At the same time, silver ions react with hydroxide ions in the solution. - Silver hydroxide precipitate is formed, and then aged, filtered, washed and dried to obtain a metal hydroxide material.

[0076] The soluble salts of base metals used in the raw materials of the present application are low in cost and recyclable.

[0077] In the above step 101, the water-soluble organic matter includes one or more of sucrose, glucose, PVP, sodium carboxymethyl cellulose, polyethylene, polypropylene, mannose, starch, chitosan, dextran, oxalic acid and boric acid. The organic carbon source used is a common cheap material such as sucrose, starch or sodium carboxymethyl cellulose, which improves the performance of the negative electrode material while taking into account the low cost, and is expected to be promoted industrially.

[0078] In the above step 103, the gas in the protective atmosphere includes one or more of nitrogen, argon, neon, krypton, and xenon.

[0079] In the above step 103, during the carbonization treatment, the heating rate is 0.5-20°C / min, the calcination temperature is 500-1100°C, and the calcination time is 50-600min.

[0080] In the above step 103, after the carbonization treatment, the preparation method further comprises:

[0081] Under a protective atmosphere, a phosphating treatment is performed so that the three-dimensional porous carbon composite material further includes metal phosphide particles embedded in the three-dimensional porous carbon framework.

[0082] See also Figure 3 As shown, the phosphating treatment adds metal phosphide particles 15 to the three-dimensional porous carbon skeleton 11, and the two kinds of alkali-philic metallic substances, the metal phosphide particles 15 and the elemental particles 13, are evenly distributed in the three-dimensional porous carbon skeleton 11, thereby preparing a three-dimensional porous carbon composite material with adjustable alkali metal deposition.

[0083] Wherein, in the phosphating treatment, the phosphorus source used includes one or more of phosphate, metaphosphate, hypophosphite and phosphorus pentoxide.

[0084] It is understandable that during the above-mentioned phosphating treatment, there are various sources of metal phosphide particles. For example, part of the phosphorus source may be directly embedded in the three-dimensional porous carbon skeleton during the phosphating treatment to form the metal phosphide particles. For another example, part of the phosphorus source may react with part of the elemental particles during the phosphating treatment, such as silver phosphide, to form the metal phosphide particles. For another example, when the metal hydroxide is prepared by the above-mentioned homemade method, it may also contain a certain amount of base metal hydroxide. During the phosphating treatment, part of the phosphorus source may react with the base metal to generate the phosphide of the base metal, such as copper phosphide, to form the metal phosphide particles.

[0085] The mass ratio of the phosphorus source used in the phosphating treatment to the product after the spray-dried product is carbonized is 1: (0.2-50).

[0086] In the phosphating treatment, the heating rate is 0.5-20°C / min, and the phosphating temperature is 200°C-500°C.

[0087] Furthermore, after the phosphating treatment, the preparation method further comprises: washing with acid solution to remove impurities, and drying.

[0088] Wherein, the acid solution includes one or more of dilute hydrochloric acid, dilute sulfuric acid and glacial acetic acid.

[0089] Further, see Figure 2 As shown, an embodiment of the present application also provides a three-dimensional porous carbon composite material, which includes a three-dimensional porous carbon skeleton, and single particles of metal elements of alkali-philic metals embedded in the three-dimensional porous carbon skeleton, or the three-dimensional porous carbon composite material includes a three-dimensional porous carbon skeleton, and metal phosphide particles and single particles of metal elements of alkali-philic metals embedded in the three-dimensional porous carbon skeleton.

[0090] It is understandable that the above three-dimensional porous carbon composite material can be prepared by using the above three-dimensional porous carbon composite material preparation method.

[0091] Further, see Figure 3 As shown, an embodiment of the present application further provides a three-dimensional porous carbon-alkali metal composite material, which includes a three-dimensional porous carbon composite material and an alkali metal, wherein the alkali metal is embedded in a three-dimensional porous carbon skeleton.

[0092] Furthermore, an embodiment of the present application also provides a method for preparing a three-dimensional porous carbon-alkali metal composite material, which comprises: introducing alkali metal into the three-dimensional porous carbon skeleton by electrodeposition, electrochemical method or melting method.

[0093] The electrochemical method refers to using a three-dimensional porous carbon composite material as an active material, adding a conductive agent and a binder to prepare a slurry, and then coating it on a current collector to prepare a positive electrode sheet, using an alkali metal as a negative electrode to prepare a battery, and depositing the alkali metal into the three-dimensional porous carbon skeleton through discharge.

[0094] The melting method refers to mixing the alkali metal and the three-dimensional porous carbon composite material in an inert gas environment and heating them to above the melting point of the alkali metal, so as to spontaneously embed the alkali metal by relying on the fluidity of the molten state of the alkali metal.

[0095] The electroplating method refers to adding a three-dimensional porous carbon composite material into an electrolyte, using an external voltage to migrate alkali metal ions into the three-dimensional porous carbon composite material, and causing the alkali metal ions to be deposited in the three-dimensional porous carbon composite material.

[0096] Furthermore, an embodiment of the present application also provides a negative electrode, which includes the above-mentioned three-dimensional porous carbon composite material, and / or a three-dimensional porous carbon alkali metal composite material.

[0097] That is to say, the negative electrode provided in the embodiments of the present application can be prepared using the above-mentioned three-dimensional porous carbon composite material as the active material, or using the above-mentioned three-dimensional porous carbon alkali metal composite material as the active material, or using the above-mentioned three-dimensional porous carbon composite material and three-dimensional porous carbon alkali metal composite material as active materials at the same time, or using the above-mentioned three-dimensional porous carbon composite material mixed with other existing negative electrode active materials, or using the above-mentioned three-dimensional porous carbon alkali metal composite material mixed with other existing negative electrode active materials, or using the above-mentioned three-dimensional porous carbon composite material and three-dimensional porous carbon alkali metal composite material mixed with other existing negative electrode active materials.

[0098] Furthermore, an embodiment of the present application also provides a battery, which includes the above-mentioned negative electrode, that is, a battery assembled using the above-mentioned negative electrode, and the battery can be one of an alkali metal sulfur battery, an alkali metal air battery, an alkali metal battery, and an alkali metal ion battery.

[0099] The present application is applied to lithium-sulfur batteries, which can effectively inhibit the dissolution and shuttling of lithium polysulfide. The metal phosphide can catalyze the conversion of lithium polysulfide and also has a high electrical conductivity, which can simultaneously improve the rate performance and cycle performance of the lithium-sulfur battery.

[0100] It is understandable that the above-mentioned battery may use a liquid electrolyte or a solid electrolyte.

[0101] The present application is further described in detail below in conjunction with the embodiments, which are only used to explain the present application and do not mean that the present application is limited to the following embodiments.

[0102] Example 1

[0103] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0104] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time, and control the pH value to 9.3 during the process. Stop when the total molar amount of ammonia water and the total molar amount of sulfate in the added mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90℃ for 10 hours to obtain a metal hydroxide precipitate.

[0105] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0106] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0107] Example 2

[0108] Compared with Example 1, the only difference is that the mass ratio of sodium trimetaphosphate to porous silver-carbon material is 2:1, specifically:

[0109] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0110] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0111] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 2:1. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0112] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0113] Example 3

[0114] Compared with Example 1, the only difference is that the mass ratio of sodium trimetaphosphate to porous silver-carbon material is 1:100, specifically:

[0115] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0116] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0117] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, with a mass ratio of sodium trimetaphosphate to PVP of 1:100, and then argon was introduced and heated to 400°C for phosphating.

[0118] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0119] Example 4

[0120] Compared with Example 1, the only difference is that phosphating is not performed, specifically:

[0121] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0122] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0123] The metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nano-silver particles.

[0124] The carbonized product was placed in a dilute sulfuric acid solution and stirred for 1 h, filtered, washed, and dried for 5 h to obtain a three-dimensional porous silver-carbon composite material.

[0125] Example 5

[0126] Compared with Example 1, the only difference is that the phosphating temperature is 200°C, specifically:

[0127] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0128] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0129] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 200°C for phosphating.

[0130] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0131] Example 6

[0132] Compared with Example 1, the only difference is that the phosphating temperature is 300°C, specifically:

[0133] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0134] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value ratio of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0135] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 300°C for phosphating.

[0136] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0137] Example 7

[0138] Compared with Example 1, the only difference is that the phosphating temperature is 500°C, specifically:

[0139] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0140] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0141] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The product obtained by spray drying was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Then argon gas was introduced and the temperature was raised to 500°C for phosphating.

[0142] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0143] Example 8

[0144] Compared with Example 1, the only difference is that copper sulfate is replaced with ferrous sulfate, specifically:

[0145] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of ferrous sulfate and silver nitrate, wherein the molar ratio of ferrous sulfate to silver nitrate is 1:2, and the total molar concentration of ferrous sulfate and silver nitrate is 0.05 mol / L.

[0146] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0147] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0148] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0149] Example 9

[0150] Compared with Example 8, the only difference is that the carbonization temperature is 600°C, specifically:

[0151] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of ferrous sulfate and silver nitrate, wherein the molar ratio of ferrous sulfate to silver nitrate is 1:2, and the total molar concentration of ferrous sulfate and silver nitrate is 0.05 mol / L.

[0152] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0153] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 600°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0154] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0155] Example 10

[0156] Compared with Example 8, the only difference is that the carbonization temperature is 1000°C, specifically:

[0157] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of ferrous sulfate and silver nitrate, wherein the molar ratio of ferrous sulfate to silver nitrate is 1:2, and the total molar concentration of ferrous sulfate and silver nitrate is 0.05 mol / L.

[0158] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0159] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 1000°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0160] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0161] Embodiment 11

[0162] Compared with Example 1, the only difference is that the pH value of the base liquid is adjusted to 11, and the pH value is maintained at 11 during the reaction, specifically:

[0163] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0164] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 11 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 11. Stop when the total molar amount of ammonia water and the total molar amount of sulfate in the added mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0165] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0166] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0167] Example 12

[0168] Compared with Example 11, the only difference is that the pH value of the base liquid is adjusted to 6, and the pH value is maintained at 6 during the reaction, specifically:

[0169] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0170] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 6 to obtain a base liquid. Stir under the protection of nitrogen, and add solution A and mixed solution C to the base liquid at the same time. During the process, the pH value of the mixed solution is controlled to be 6. Stop when the total molar amount of ammonia water and the total molar amount of sulfate in the added mixed solution C are 5:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90°C for 10 hours to obtain a metal hydroxide precipitate.

[0171] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0172] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0173] Embodiment 13

[0174] Compared with Example 1, the only difference is that the molar ratio of ammonia water to the molar ratio of sulfate in the mixed solution is 20:1, specifically:

[0175] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0176] First, prepare ammonia water A, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain the base solution. Stir under the protection of nitrogen, and add solution A, solution B and solution C at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 20:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90℃ for 10 hours to obtain a metal hydroxide precipitate.

[0177] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0178] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0179] Embodiment 14

[0180] Compared with Example 13, the only difference is that the molar ratio of ammonia water to the molar ratio of sulfate in the mixed solution is 1:1, specifically:

[0181] Prepare ammonia water A with a concentration of 1 mol / L, prepare a dilute sulfuric acid solution B with a concentration of 0.5 mol / L, and prepare a mixed solution C of copper sulfate and silver nitrate, wherein the molar ratio of copper sulfate to silver nitrate is 1:2, and the total molar concentration of copper sulfate and silver nitrate is 0.05 mol / L.

[0182] Prepare ammonia water A first, and use dilute sulfuric acid solution B to adjust the pH value to 9.3 to obtain the base solution. Stir under the protection of nitrogen, and add sodium hydroxide solution and solution C at the same time. During the process, the pH value of the mixed solution is controlled to be 9.3. Stop when the total molar amount of ammonia water and the total molar amount of sulfate added to the mixed solution C are 1:1. After the reaction is completed, age for 3 hours, filter, wash with distilled water three times, and vacuum dry at 90℃ for 10 hours to obtain a metal hydroxide precipitate.

[0183] Metal hydroxide and PVP were mixed in water at a mass ratio of 1:2, stirred for 3 hours, and then spray dried. The spray-dried product was carbonized at high temperature, heated to 800°C at a heating rate of 5°C / min, and calcined to obtain a porous silver-carbon material embedded with nanosilver particles. After cooling, sodium trimetaphosphate was placed in the upper airflow direction of the porous silver-carbon material, and the mass ratio of sodium trimetaphosphate to the porous silver-carbon material was 1:10. Argon was then introduced and the temperature was raised to 400°C for phosphating.

[0184] The phosphating product was placed in a dilute sulfuric acid solution and stirred for 1 hour, filtered, washed, and dried for 5 hours to obtain a three-dimensional porous silver-carbon composite material.

[0185] Embodiment 15

[0186] Compared with Example 1, the only difference is that commercially available AgOH and PVP are mixed in water at a mass ratio of 1:2.

[0187] The material prepared in the above embodiment was mixed with a conductive agent and a binder to form a slurry and applied to prepare a pole piece. The pole piece was used as the positive electrode and a metal lithium sheet was used as the negative electrode to prepare and assemble a button battery. The voltage range was set to 0.1-1V and the test was carried out at a current of 100mA / g.

[0188] The test results are shown in Table 1:

[0189] Table 1

[0190] First coulombic efficiency 80-cycle Coulomb efficiency 80-cycle capacity retention rate Example 1 90.3% 99.2% 91% Example 2 88.6% 94.2% 77% Example 3 87.2% 95.6% 79% Example 4 84.9% 95.0% 78% Example 5 88.9% 96.0% 82% Example 6 90.1% 99.0% 90% Example 7 88.6% 96.7% 84% Example 8 88.2% 97.0% 88% Example 9 86.2% 94.4% 83% Example 10 87.0% 96.8% 87% Embodiment 11 86.8% 96.9% 86% Example 12 86.1% 95.5% 85% Embodiment 13 85.6% 93.3% 75% Embodiment 14 89.6% 88.5% 79% Embodiment 15 89.6% 97.8% 89%

[0191] In Example 4, only carbonization treatment was performed without phosphating treatment, and its first coulombic efficiency could reach 84.9%, 80-cycle coulombic efficiency reached 85%, and 80-cycle capacity retention rate reached 78%. It can be seen that when carbonization is performed in this application, the generation of gas forms a three-dimensional porous carbon skeleton with uniform pores, large specific surface area, and high porosity, which provides a location for the deposition of alkali metals, and at the same time reserves space for the volume change of alkali metals during the charge and discharge process, reduces the occurrence of side reactions caused by material breakage, reduces the expansion of the negative electrode, and increases the cycle life. Silver particles are evenly distributed inside the three-dimensional porous carbon skeleton. The embedded silver particles can induce the uniform deposition of alkali metals inside the three-dimensional porous carbon skeleton due to the affinity of alkali metals, which regulates the uniformity of alkali metal deposition under high current, reduces the formation of dendrites, and improves safety. The high specific surface area of ​​the three-dimensional porous carbon skeleton effectively increases the reaction sites with the electrolyte, thereby improving the rate performance of the battery.

[0192] Furthermore, by comparing Example 1 with Example 2, Example 3, and Example 4, it can be seen that when phosphating treatment is further performed, the two kinds of alkali-philic metallic substances, metal phosphide particles and silver particles, are evenly distributed in the three-dimensional porous carbon skeleton, so that the first coulomb efficiency, 80-cycle coulomb efficiency, and 80-cycle capacity retention rate of Example 1, Example 2, and Example 3 can be greatly improved. The three-dimensional porous silver-carbon composite material prepared when the mass ratio of sodium trimetaphosphate to porous silver-carbon material is 1:10 has the best cycle performance and coulomb efficiency. In contrast, when the mass ratio of sodium trimetaphosphate to porous silver-carbon material is 2:1, excessive phosphorus content affects the stability of the electrode.

[0193] It can be seen from Examples 1, 5, 6 and 7 that the phosphating temperature is 300°C-400°C, which is a more suitable phosphating temperature. When the phosphating temperature is too low, it will affect the smooth progress of the phosphating reaction to a certain extent, reduce the first coulomb efficiency, 80-cycle coulomb efficiency and 80-cycle capacity retention rate. When the phosphating temperature is too high, it will also affect the cycle performance of the material to a certain extent.

[0194] By comparing Example 1 with Example 8, it can be seen that the performance of the template-synthesized silver-carbon composite material prepared by copper sulfate and silver nitrate solution is better than that of ferrous sulfate and silver nitrate solution. Copper ions show better lithium affinity than ferrous ions.

[0195] By comparing Example 8 with Example 9 and Example 10, it can be seen that 800°C is a suitable carbonization temperature. If the carbonization temperature is too low, the material is not completely carbonized, and other element components affect the performance of the material. The electrochemical performance of the material obtained at a carbonization temperature of 1000°C is not much different from that of the material obtained at 800°C, but too high a temperature will lead to a waste of energy and increase costs.

[0196] By comparing Example 1 with Example 11 and Example 12, when the pH value of the mixed solution is maintained at 9.3, the obtained material has the best performance. Too low a pH value will lead to a waste of silver ions.

[0197] By comparing Example 1 with Example 13 and Example 14, it can be seen that the performance is excellent when the molar ratio of ammonia water to copper is 5: 1. If the ammonia water content is low, it cannot be completely complexed with copper ions, and if the content is too high, the silver hydroxide precipitate will dissolve.

[0198] By comparing Example 1 and Example 15, it can be seen that Example 15 has a decrease in the first coulombic efficiency, 80-cycle coulombic efficiency and 80-cycle capacity retention rate. The reason may be: compared with Example 15 which uses commercially available pure AgOH, when the self-made AgOH precipitate is prepared by Example 1, the obtained metal hydroxide precipitate contains not only AgOH precipitate, but may also contain base metal hydroxide precipitate. The presence of a small amount of base metal hydroxide can enhance the lithium affinity of the silver-carbon material, reduce the formation of lithium dendrites, and improve the capacity retention rate of the battery.

[0199] In summary, in this application, alkali metals with high theoretical capacity of 3860mAh / g and low voltage are combined with carbon materials with high cycle stability and safety performance to prepare three-dimensional porous carbon composite materials and three-dimensional porous carbon alkali metal composite materials with better electrochemical performance. The prepared material has a capacity much higher than the theoretical capacity of 372mAh / g of graphite because of its stable alkali metal embedding sites, thereby effectively improving the energy density of the battery. At the same time, the material has the ability to induce alkali metal deposition, which reduces the formation of dendrites by inducing uniform deposition of alkali metals, and obtains better cycle performance and safety performance than previous alkali metal batteries.

[0200] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a three-dimensional porous carbon composite material, characterized in that: It includes: Mixing a metal hydroxide and a water-soluble organic matter in water by stirring to obtain a slurry, wherein the metal hydroxide includes a hydroxide of a metal element of an alkali-philic metal; spray drying the slurry to obtain a spray-dried product; The spray-dried product is carbonized under a protective atmosphere to obtain a three-dimensional porous carbon composite material.

2. The method for preparing the three-dimensional porous carbon composite material according to claim 1, characterized in that: The metal elements that are alkali-philic include silver (Ag).

3. The method for preparing the three-dimensional porous carbon composite material according to claim 2, characterized in that: The hydroxide of the metal element that is alkaliphilic is silver hydroxide; The preparation method further comprises the following steps of preparing a metal hydroxide: Adjusting ammonia water to a preset pH value to obtain a base solution; Adding a mixed solution containing a soluble salt of a base metal and silver nitrate to the base solution, and adding ammonia water to generate a complex and a precipitate; Aging, filtering, washing and drying can obtain metal hydroxide.

4. The method for preparing the three-dimensional porous carbon composite material according to claim 3, characterized in that: The concentration of the ammonia water is 0.02 mol / L to 20 mol / L.

5. The method for preparing the three-dimensional porous carbon composite material according to claim 3, characterized in that: The preset pH value is 6-11.

6. The method for preparing the three-dimensional porous carbon composite material according to claim 3, characterized in that: The base metal includes one or more of nickel, iron, copper, zinc, aluminum and manganese.

7. The method for preparing the three-dimensional porous carbon composite material according to claim 3, characterized in that: The soluble salts of base metals include one or more of sulfates and nitrates.

8. The method for preparing the three-dimensional porous carbon composite material according to claim 3, characterized in that: The molar ratio of base metal ions to silver ions in the mixed solution is 1:0.1-10.

9. The method for preparing the three-dimensional porous carbon composite material according to claim 3, characterized in that: The molar ratio of the total amount of ammonia water to the soluble salt of the base metal is 1:0.05-20.

10. The method for preparing the three-dimensional porous carbon composite material according to claim 1, characterized in that: The water-soluble organic matter includes one or more of sucrose, glucose, PVP, sodium carboxymethyl cellulose, polyethylene, polypropylene, mannose, starch, chitosan, dextran, oxalic acid and boric acid.

11. The method for preparing the three-dimensional porous carbon composite material according to claim 1, characterized in that: The mass ratio of the metal hydroxide to the water-soluble organic matter is 1:0.01-100.

12. The method for preparing the three-dimensional porous carbon composite material according to claim 1, characterized in that: In the carbonization treatment, the heating rate is 0.5-20°C / min, the calcination temperature is 500-1100°C, and the calcination time is 50-600min.

13. The method for preparing the three-dimensional porous carbon composite material according to claim 1, characterized in that: After the carbonization treatment, the preparation method further comprises: Under a protective atmosphere, a phosphating treatment is performed so that the three-dimensional porous carbon composite material further includes metal phosphide particles embedded in the three-dimensional porous carbon framework.

14. The method for preparing the three-dimensional porous carbon composite material according to claim 13, characterized in that: In the phosphating treatment, the phosphorus source used includes one or more of phosphate, metaphosphate, hypophosphite and phosphorus pentoxide.

15. The method for preparing the three-dimensional porous carbon composite material according to claim 13, characterized in that: The mass ratio of the phosphorus source used in the phosphating treatment to the product after the spray-dried product is carbonized is 1: (0.2-50).

16. The method for preparing the three-dimensional porous carbon composite material according to claim 13, characterized in that: In the phosphating treatment, the heating rate is 0.5-20°C / min, and the phosphating temperature is 200°C-500°C.

17. The method for preparing the three-dimensional porous carbon composite material according to claim 13, characterized in that: After the phosphating treatment, the preparation method further comprises: Wash with acid and dry.

18. The method for preparing the three-dimensional porous carbon composite material according to claim 17, characterized in that: The acid solution includes one or more of dilute hydrochloric acid, dilute sulfuric acid and glacial acetic acid.

19. A three-dimensional porous carbon composite material, characterized in that: The three-dimensional porous carbon composite material comprises: Three-dimensional porous carbon framework; And, single substance particles of metal elements of alkali-philic metals embedded in the three-dimensional porous carbon skeleton, or metal phosphide particles and single substance particles of metal elements of alkali-philic metals embedded in the three-dimensional porous carbon skeleton.

20. A three-dimensional porous carbon-alkali metal composite material, characterized in that: It includes: A three-dimensional porous carbon composite material as claimed in claim 19, or a three-dimensional porous carbon composite material prepared by the method for preparing a three-dimensional porous carbon composite material as claimed in any one of claims 1 to 18; and an alkali metal embedded in the three-dimensional porous carbon framework.

21. A method for preparing the three-dimensional porous carbon-alkali metal composite material as claimed in claim 20, characterized in that: It includes: The alkali metal is introduced into the three-dimensional porous carbon framework by electrodeposition, electrochemical method or melting method.

22. A negative electrode, characterized in that: It comprises the three-dimensional porous carbon composite material as claimed in claim 19 and / or the three-dimensional porous carbon-alkali metal composite material as claimed in claim 20.

23. A battery, characterized in that: It includes the negative electrode as claimed in claim 22.